RIGID FLEXIBILITY: SEEING THE OPPORTUNITIES IN “FAILED” QUALITATIVE RESEARCH - CohenMiller, Anna S.; Schnackenberg, Heidi; Demers, Denise (International Journal of Qualitative Methods, 2020)
This article highlights an experience of “failing” within a qualitative research study. Specifically, the authors speak to the failure of recruiting participants in conducting synchronous video and telephone interviews. Drawing from literature in business and examples from research method texts to demonstrate the cross-disciplinary concerns and insights of failure within one’s work, the authors discuss how failure can be reframed as opportunity through the lens of “rigid flexibility” and the innovative steps they implemented. Providing additional insight into the process of framing and reframing failure in research, the authors integrate poetic inquiry as a tool for reflection to highlight their process and suggested steps for new researchers. The authors argue that researchers can approach studies with the idea that failures in the planning and/or execution can lead to opportunities and new insights
Keywords: Type of access: Open Access; rigid flexibility; online research; qualitative research methods; synchronous and asynchronous interviewing; texting; video-conference; cross-disciplinary